Within group and between group comparisons of political and apolitical voters of Bangladesh with personality dimension of authoritarianism (Journal of Life and Earth Science, 2011)
The study attempted to measure authoritarianism, as related to political-apolitical group composition, male-female gender recognition and urban-rural residential background of the subjects. Kool's (1980) authoritarian scale was used. A total of 320 subjects were equally divided into political and apolitical groups. Thus a 2×2×2 factorial design involving 2 levels of group composition (political vs. apolitical), 2 levels of gender (male vs. female) and 2 levels of residential background (urban vs. rural) was used. Results were analyzed using t-tests on the scores of authoritarian scale. Although no significant difference was obtained between political and apolitical groups (N=160), within-group comparisons revealed that urban females of political affiliation were more authoritarian than the urban males, rural males and rural females (N=40 for each). Again urban females of apolitical group were found more authoritarian than urban males, rural males and rural females (N=40 for each). A comparison between groups of political and apolitical subjects revealed that urban females of political group were more authoritarian than rural males and rural females of apolitical groups (N=40 for each). On the other hand, urban females of apolitical group were found more authoritarian than urban males, rural males and rural females of political affiliation. Irrespective of gender, political urban subjects were more authoritarian than apolitical rural subjects (N=80) while apolitical urban subjects were more authoritarian than political rural subjects (N=80). Key words: Political and apolitical voters; authoritarianism; personality dimension; Kool's authoritarian scale DOI: 10.3329/jles.v5i0.7353 J. Life Earth Sci., Vol. 5: 69-73, 2010